2016
DOI: 10.1080/09540121.2016.1211614
|View full text |Cite
|
Sign up to set email alerts
|

Someone to count on: social support as an effect modifier of viral load suppression in a prospective cohort study

Abstract: Though functional social support has been shown to serve as a protective factor for HIV viral load suppression in other populations, scant research has examined this relationship among men who have sex with men (MSM) in the United States. We assessed characteristics of social support; effects of social support on HIV viral load; and moderation by social support of the relationship between psychosocial indicators of a synergistic epidemic (syndemic) and HIV viral load. We analyzed longitudinal data from HIV-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
67
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 55 publications
4
67
1
Order By: Relevance
“…There is consistent evidence that social networks exert strong social influence on the engagement of network members in the HIV Care Continuum 2123 . In addition to stigma affecting HIV infection, MSM often are affected by stigma related to sexual practices and sexual orientation 24,25 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is consistent evidence that social networks exert strong social influence on the engagement of network members in the HIV Care Continuum 2123 . In addition to stigma affecting HIV infection, MSM often are affected by stigma related to sexual practices and sexual orientation 24,25 .…”
Section: Discussionmentioning
confidence: 96%
“…Stigma is a fundamental barrier to engagement into HIV care and negatively impacts patient outcomes 11,12 . Social support systems reduce stigma, improve individual acceptability of HIV infection, as well as successful navigation throughout the HIV Care Continuum pathway 23,26 . Instrumental support such as provision of financial assistance, emotional support such as comfort, and informational support such as advice on dealing with difficult situation may have facilitated the uptake of HIV testing, initiation of ART and eventual viral suppression in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among PLWH, social support is directly and indirectly associated with greater treatment adherence (DiIorio et al, 2009; Kelly, Hartman, Graham, Kallen, & Giordano, 2014; Woodward & Pantalone, 2012). Greater social support (perceived and received social support) is associated with lower viral load and greater viral suppression among PLWH (Amberbir, Woldemichael, Getachew, Girma, & Deribe, 2008; Friedman et al, 2017; Simoni, Frick, & Huang, 2006). Furthermore, at the time of HIV diagnosis, social support may be a critical factor in facilitating initiation and engagement in HIV care (Lauby et al, 2012), facilitating ART adherence (Latkin et al, 2013), and improving coping with HIV-related stressors (Lam, Naar-King, & Wright, 2007; Power et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, research has indicated that the availability of social support may be limited for some African Americans (Friedman et al, 2017), who are more likely to report smaller social networks compared with White men (Kapadia et al, 2013). This may stem, in part, from stigma, a pervasive social process which is negatively associated with social support among PLWH (Farber, Lamis, Shahane, & Campos, 2014; Mak et al, 2007; Simbayi et al, 2007; Simbayi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the key to the success of the two intervention strategies is adequate adherence to treatment and PrEP. Because the life-long use of anti-viral drugs requires sufficient support from social network and environment (policy support and medical service) (59), the social network factors embedded in the environments of users may either facilitate and/or impeded adherence. HIV/AIDs interventions need to address the three types of social networks around mid-age FSWs, the structures of networks, redundant and non-redundant connections, and their environmental resources.…”
Section: Discussionmentioning
confidence: 99%